Laparoendoscopic single-site surgery for adnexal disease during pregnancy: A single-center preliminary experience - Yin, Min; Yang, Jiaxin; Zhou, Huimei; Zhang, Xinyue (Frontiers in Surgery, 2022)
Purpose This study aimed to evaluate the safety and efficacy of laparoendoscopic single-site surgery (LESS) in treating adnexal disease during pregnancy. Methods Medical records of included patients were retrospectively reviewed and follow-ups of all the patients were performed until the delivery of the fetus. The clinical characteristics, surgical interventions, postoperative complications, and pregnancy outcomes were analyzed. Results Six cases were included, with the gestational age ranging from 19 to 31 weeks 1 day. Procedures included salpingo-oophorectomy (n = 3), ovarian or paratubal cystectomy with detorsion (n = 2), and adnexal detorsion (n = 1). The median duration of surgery was 35 min (range, 20–60 min), and the estimated blood loss ranged from 5 to 50 ml. No major intraoperative or postoperative complications were noted. The final pathologic results included high-grade serous ovarian carcinoma, ovarian borderline serous cystadenoma, ovarian simple cyst, endometrioma, and mesosalpinx cyst. Five patients had a spontaneous vaginal delivery at full-term, and one patient had a cesarean section preterm followed by comprehensive staging surgery of ovarian cancer. Conclusion Based on the data we included, LESS performed by experienced surgeons appeared to be a safe and feasible alternative to multiport laparoscopic surgery for the management of selected patients with adnexal disease during pregnancy. More studies with large sample sizes at multiple centers are warranted.